2019
DOI: 10.1088/1755-1315/347/1/012075
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical content, extract standardization and antioxidant activity of Calliandra calothyrsus Meissn leaf, a potential phytoestrogen source

Abstract: Calliandra ( Calliandra calothyrsus Meissn.) is a leguminous shrubs that almost spread throughout the area of Bali island, especially the area of Baturiti, Tabanan. The ethanol extract of 80% of C. calothyrsus leaves is a potential source of exogenous estrogen in terms of its phytoestrogen content. Potential extract of potassium which is very useful can be consumed in the form of phytopharmaca preparations. One of the requirements to prepare the formulation of phytopharm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Phenolic compound is the largest antioxidants contributor in C. calothyrsus leaf extract. The IC 50% value of 29.6 mg sample of C. calothyrsus leaf extract was 156 ppm (Setyawati et al, 2019). This antioxidant activity value proved that C. calothyrsus was a potential antioxidant.…”
Section: Effect Of C Calothyrsus On Uterine Wall Thicknessmentioning
confidence: 64%
See 2 more Smart Citations
“…Phenolic compound is the largest antioxidants contributor in C. calothyrsus leaf extract. The IC 50% value of 29.6 mg sample of C. calothyrsus leaf extract was 156 ppm (Setyawati et al, 2019). This antioxidant activity value proved that C. calothyrsus was a potential antioxidant.…”
Section: Effect Of C Calothyrsus On Uterine Wall Thicknessmentioning
confidence: 64%
“…calothyrsus leaf extract contains phytoestrogen, flavonoid, which have an OH group. The composition of flavonoid contained in C. calothyrsus leaf extract was thought to be similar to endogenous estrogen (Setyawati et al, 2019), so that it was able to bind to estrogen receptors (ERs) on target cells that affect the number of glands and the thickness of the endometrial layer.…”
Section: Effect Of C Calothyrsus On Uterine Wall Thicknessmentioning
confidence: 99%
See 1 more Smart Citation
“…Calliandra calothyrsus Meisn. is a small leguminous shrub that is predominantly cultivated as fodder for ruminant livestock (Setyawati et al, 2019) but other uses are also found within different farming systems and include the provision of green manure, fuel wood, shade for coffee and tea, land rehabilitation, erosion control, and honey production (Setyawati et al, 2019;Abia et al, 2006). Sesbania sesban (L.) Merrill is a multipurpose tree that is widely distributed in tropics and subtropics of Africa and Asia and usually planted by smallholder farmers mostly for its fodder and soil improvement values (Nigussie and Alemayehu, 2014; Mythili and Ravindhran, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, appreciable knowledge has been accumulated and different classes of allelochemicals have been identified in the species Calliandra calothyrsus Meisn, Senna siamea L. and Gliricidia sepium (Jacq.). Phytochemical studies carried out on those three species have shown the presence of tannins, flavonoids, terpenoids, alkaloids, steroids, phenolic compounds, anthraquinones, leucoanthocyanin, saponins and flavonol glycosides [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. However, the abundance detected for the different allelochemical molecules was variable according to these authors.…”
mentioning
confidence: 99%